Biologic therapies in autoimmune diseases - Penn, Henry (Clin Med (Lond), 2006)
Over the past decade, the treatment of rheumatoid arthritis has been revolutionised by the development of therapies targeted at molecules involved in driving the inflammatory response. This review briefly summarises the established uses of biologic therapies in rheumatoid disease, and outlines other diseases in rheumatology and other fields where biologic agents are finding a role.